Rancang Bangun Sistem Informasi Koperasi Berbasis Web Pada Koperasi Ikitama Jakarta - Kurniawan Prasetyo; Suharyanto . Suharyanto (Universitas Bina Sarana Informatika, 2019)
PT Indolife Pensiontama is a life insurance and pension fund corporation. IKITAMA Cooperation which is acronym of Indolife Pensiontama Employee Association Cooperation is a cooperation organization that having all permanent and active employees as members, in a routin activity IKITAMA Cooperative management manage daily transactions by manual using Microsoft Excel. If there is a new employee or not employed anymore then the record will be updated manually, and also there is no integration with existing human resource system, and all the data saved in Excel File without detail information. With all these problems so the author purpose to make a design and development of web-based cooperation information system. The design using object analytics oriented method by Unified Modeling Language (UML), C# .Net programming language with Microsoft Visual Studio 2012 as text editor and compiler and Microsoft SQL Server for the Database system. Keywords: Information System, Cooperation, IKITAMA.